Myxovirus resistance 1 (MX1) is an independent predictor of poor outcome in invasive breast cancer - Aljohani, Abrar I. (Breast Cancer Res Treat, 2020)
BACKGROUND: Breast cancer (BC) is a disease with variable morphology, clinical behaviour and response to therapy. Identifying factors associated with the progression of early-stage BC can help understand the risk of metastasis and guide treatment decisions. Myxovirus resistance 1 (MX1), which is involved in the cellular antiviral mechanism, plays a role in some solid tumours; however, its role in invasive BC remains unknown. In this study, we aimed to explore the clinicopathological and prognostic significance of MX1 in BC. METHODS: MX1 was assessed at the protein level using tissue microarrays from a large well-annotated BC cohort (n = 845). The expression of MX1 mRNA was assessed at the transcriptomic level using the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC; n = 1980) and validated using three publicly available cohorts on Breast Cancer Gene-Expression Miner (bc-GenExMiner version 4.4). The associations between MX1 expression and clinicopathological factors, and outcome were evaluated. RESULTS: High MX1 protein expression was associated with features of aggressiveness, including large tumour size, high tumour grade, high Nottingham prognostic index scores, hormone receptor negativity and high Ki67 expression. High MX1 expression showed an association with poor patient outcome and it was an independent predictor of short BC-specific survival (p = 0.028; HR = 1.5; 95% CI = 1.0–2.2). Consistent with the protein results, high MX1 mRNA levels showed an association with features of aggressive behaviour and with shorter survival. CONCLUSION: This study identified MX1 as an independent predictor of poor outcome in patients with BC. Further functional studies are needed to investigate the biological role of MX1 in BC and its potential value as a therapeutic target. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10549-020-05646-x) contains supplementary material, which is available to authorized users.